Cofactor Role of Iodide in Peroxidase Antimicrobial Action Against Escherichia coli - Thomas, Edwin L. (1978)
The mechanism of antimicrobial activity of the peroxidase-hydrogen peroxide (H(2)O(2))-iodide (I(−)) system was investigated. Inhibition of respiration and loss of viability of Escherichia coli were used as measures of antimicrobial activity. Because the bacteria destroyed H(2)O(2), peroxidase antimicrobial action depended on the competition for H(2)O(2) between the bacteria and the peroxidase. Utilization of H(2)O(2) by the peroxidase was favored by (i) increasing either the peroxidase or the I(−) concentration, so as to increase the rate of oxidation of I(−), (ii) lowering the temperature to lower the rate of destruction of H(2)O(2) by the bacteria, and (iii) adding H(2)O(2) in small increments so as to avoid a large excess of H(2)O(2) relative to I(−). When utilization of H(2)O(2) by the peroxidase system was favored, the peroxidase system and iodine (I(2)) were equivalent. That is, antimicrobial action per mole of H(2)O(2) equaled that per mole of I(2). Also, identical antimicrobial action was obtained either by incubating the bacteria directly with the peroxidase system or by preincubating the peroxidase system so as to form I(2) and then adding the bacteria. On the other hand, peroxidase antimicrobial action could be obtained at low I(−) concentrations. These I(−) concentrations were lower than the concentration of I(2) that was required for antimicrobial action. It is proposed that peroxidase-catalyzed oxidation of I(−) yields I(2), which reacts with bacterial components to yield the oxidized components and I(−). The I(−) that is released can be reoxidized and participate again in the oxidation of bacterial components. In this way, I(−) acts as a cofactor in the peroxidase-catalyzed oxidation of bacterial components.